International payments problems : a symposium by the American Enterprise Institute, Washington, D.C., September 23 and 24, 1965 - American Enterprise Institute for Public Policy Research (Washington DC : American Enterprise Institute for Public Policy Research, 1966)
This volume contains the proceedings of a symposium held in Washington, D.C in September 1965, by the American Enterprise Institute for Public Policy Research. The Institute's purpose in organizing the symposium was to have a responsible discussion of an important policy matter of current and prospective, major, national significance.
A symposium sponsored by the American Enterprise Institute for Public Policy Research.
Includes bibliographical footnotes and index.
usc 11/05/2018
Loans
Keywords: Balance of payments; International finance; Foreign exchange